Arbuscular Mycorrhizal Fungi as Biofertilizers to Increase the Plant Quality of Sour-Orange Seedlings - Josefa María Navarro; Asunción Morte (Agronomy, 2024)
In addressing the agricultural challenges posed by climate change, the use of biofertilizers, derived from living organisms, promotes environmentally friendly crop cultivation, and represents an adaptive strategy for sustainable agriculture in the face of climate uncertainty. Careful selection of the arbuscular mycorrhizal fungus (AMF) would represent a crucial step in mycorrhizal inoculation, considering the varying levels of compatibility between the AMF and the host plant. This study aimed to assess the impact of two AMF species that are prevalent in citrus soils of south-eastern Spain (Rhizophagus irregularis and Funneliformis mosseae) on the Citrus aurantium seedlings’ behavior. Sour-orange plants showed a high mycorrhizal dependence regardless of the specific AMF species. Both R. irregularis and F. mosseae fungi exhibited high colonization percentages, with R. irregularis outperforming F. mosseae in root colonization. Inoculation with both AMF yielded notable growth improvements, but R. irregularis exhibited higher positive effects in the long term. The heightened P nutrition and increased chlorophyll concentration significantly enhanced the performance of AMF-inoculated plants. With F. mosseae, plants showed more pronounced improvements in P nutrition and a stronger correlation of their dry mass with P concentration; however, in general, inoculation with R. irregularis produced a higher sour-orange-plant performance. Both R. irregularis and F. mosseae fungi produced strong positive effects in sour-orange growth, which positioned them as viable biofertilizer options. These results can contribute to enhancing understanding for the development of an improved design of biofertilizers used in regions that are vulnerable to climate change, such as south-eastern Spain. This promotes a shift towards more sustainable and environmentally friendly agricultural practices by reducing dependence on chemical fertilizers.